Jiangella rhizosphaerae sp. nov., an actinomycete isolated from the rhizosphere soil of wheat (Triticum aestivum L.). Issue 5 (25th February 2019) - Han, Chuanyu; Zhao, Junwei; Shi, Haoran; Tian, Yuanyuan; Zhang, Chen; Guo, Xiaowei; Xiang, Wensheng; Wang, Xiangjing
Abstract : A novel actinomycete, designated strain NEAU-YY265 T, was isolated from rhizosphere soil of wheat ( Triticum aestivum L.) and characterized using a polyphasic approach. Phylogenetic analyses based on 16S rRNA gene sequences showed that strain NEAU-YY265 T belonged to the genus Jiangella and exhibited 16S rRNA gene sequence similarities of 99.1 and 99.1 % to Jiangella mangrovi 3SM4-07 T and Jiangella alkaliphila D8-87 T . The chemotaxonomic properties of strain NEAU-YY265 T were consistent with those of the genus Jiangella : the cell-wall peptidoglycan type was based onll - diaminopimelic acid; the whole-cell hydrolysates contained glucose, ribose and rhamnose; MK-9(H4 ) and MK-9(H2 ) were the predominant menaquinones. The novel strain produced branching mycelium which fragmented into short or elongated rods. The major fatty acids (>5 %) were anteiso-C15 : 0, anteiso-C17 : 0, C17 : 1 ω8 c, iso-C16 : 0, C17 : 0 and iso-C15 : 0 . The DNA G+C content was 72.6 mol%. Strain NEAU-YY265 T was phenotypically distinct from recognized Jiangella species and shown to belong to a separate genomic species based on DNA–DNA hybridization results. Thus, strain NEAU-YY265 T is considered to represent a novel species of the genus Jiangella, for which the name Jiangella rhizosphaerae sp. nov. is proposed. The type strain is NEAU-YY265 T (=JCM 32551 T =CGMCC 4.7475 T ).